(The role of Muslinin in the intellectual and artistic movement in the light of the Book of the Deaths of the Elders of Ibn Khalkan "d: 681 h / 1282 g)" (Journal of the College of Basic Education, 2022)
(The role of Muslinin in the intellectual and artistic movement in the light of the Book of the Deaths of the Elders of Ibn Khalkan "d: 681 h / 1282 g)" Submitted by: Dr. Shaimaa Salem Abd Al-Sahib and Dr. Sana Shendi Awan University of Mustansiriya / Faculty of Basic Education / Department of History Since the Islamic conquest of the city of Mosul in the year (16 h / 637 g) has entered the field of intellectual and cultural activity, which is the same in other Islamic cities; Islam has been a strong impetus in this regard, he said in the words of the Almighty on the request of knowledge, "God raises those who believe you and those who gave the knowledge" » Therefore, the sons of Mosul have been active in the Islamic scientific movement and they have been one of the poles of this civilization and a fundamental pillar in its development. This movement came to fruition since the first century AH especially in the field of religious sciences and then expanded during the following centuries to include all kinds of sciences. The division in the knowledge of the regions Mosul by saying: "Many kings and sheikhs are not without high attribution and a jurist mentioned"Therefore, we have seen that the tunnel on this important aspect of this ancient city by highlighting the role of the scientists of Mosul and its thinkers in the light of the book Deaths of the Elders of Ibn Khalkan (d: 681h / 1282g) is not hidden the importance of the translation books to highlight the role of scientists and give us a clear picture of the nature of the scientific movement in the country The importance of the Book of( Deaths of the Elders) is that it gave us a temporal space and a spatial space, both wide and temporal. It began with the Musallain translations from the second century until the seventh century (h) But spatial: it is possible to explain the role of Muslain whether it is within the city of Mosul and its affiliated areas or in the Islamic countries in general, not only the role of scientists and scholars of Mosul on their town, but the scientific trip, which is one of the most important pillars of the request of science at that time a role in Antvall Muslainin To the rest of the Arab Islamic country and to the arrival of the sons of other cities to MosulIn the first section we gave a brief summary of the life of Ibn Khalkan to the great writings about his life The second topic dealt with the role of Mosul scholars in the field of authorship and classification. The topic was divided into four axes that dealt with their role in the fields of jurisprudence, Hadith, language, literature and poetry, and in other fields that included history, geography and pure science The third topic: to show their role in teaching and divided into two axes: the first talked about mosques and barbarism and strangulations, and the second talked about schools The fourth topic: specialized readers and their role in this area While the fifth topic: about the movement of art and singing and the most famous singers Almmslain.